DNA methylation regulator-mediated modification pattern defines tumor microenvironment immune infiltration landscape in colon cancer - Yuan, Shijin; Gao, Yuzhen; Xia, Yan; Wang, Zhuo; Wang, Xian (Frontiers in Genetics, 2022)
Emerging evidence implies a non-negligible role of DNA methylation in tumor immunity, however, its comprehensive impact on tumor microenvironment (TME) formation and immune activation remains unclear. In this study, we integrated 24 DNA methylation regulators among 754 colon cancer patients to distinguish different modification patterns via an unsupervised clustering method, and explore their TME immune characteristics. Three DNA methylation modification patterns with distinct prognosis and biological behaviors were identified, consistent with three known phenotypes of immune-inflamed, immune-excluded, and immune-desert. We then determined a DNA methylation gene signature and constructed a DNA methylation score (DMS) to quantify modification patterns individually through principal component analysis algorithms. DMS-low group had characteristics of specific molecular subtypes, including microsatellite instability, CpG island methylator phenotype positive, and mutant BRAF, presented by increased mutation burden, activation of DNA damage repair and immune-related pathways, highly TME immune cells infiltration, and hence, a preferable prognosis. Further, low DMS was also demonstrated to be correlated to better response and prolonged survival of anti-PD-L1 antibody, indicating that DMS could be considered as an effective predictive tool for immunotherapy. In conclusion, our work presented a landscape of different DNA methylation modification patterns, and their vital role in the formation of TME diversity and complexity, which could help to enhance understanding of TME immune infiltration characteristics and more importantly, guide immunotherapy strategies more effectively and personalized.